Introduction to the 2013 Gramsci Summer School / Introduzione alla Gramsci Summer School (2013) - Pala, Mauro (International Gramsci Journal, 2023)
In the spirit of the “Gramsci Workshop” - Introducing the workshop entitled For Gramsci means in the first place to put it in the context of the International Summer School beginning in 2014: as had emerged from the preliminary discussions, the Summer School at Ghilarza (the Gramsci Summer School – hereafter the GSS) is a point of contact, an interface, but above all a field of interaction and reciprocal enrichment between the Fondazione Istituto Gramsci (Rome) and the International Gramsci Society, thanks to the collaboration of the Antonio Gramsci House Museum in Ghilarza and of the other Gramsci associations, not forgetting the essential contribution of the Fondazione Banca di Sardegna.